PLANTING OF FAMILY MEDICINAL PLANTS (TOGA) IN SIBREH KEUMUDEE KEC. SUKA MAKMUR KAB. ACEH BESAR: PENANAMAN TANAMAN OBAT KELUARGA (TOGA) DI DESA SIBREH KEUMUDEE KECAMATAN SUKA MAKMUR KABUPATEN ACEH BESAR - Erda Marniza; Resmila Dewi; Rina Kurniaty (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
Indonesia has recognized and used medicinal plants as an effort to overcome health problems, long before health services with modern medicines were known to the public. Currently, natural treatment using medicinal plants is becoming a trend in society, one of the efforts to increase natural treatment is the planting and utilization of Family Medicinal Plants (TOGA) program in Sibreh Keumudee village, Suka Makmur subdistrict, Aceh Besar district. The aim of this service is to improve health by using TOGA, caring for the environment and the benefits of TOGA. The method used is planting plants. The implementation of TOGA planting as one of the service programs with the theme "Use of Medicinal Plants for the Prevention and Treatment of Disease" has been carried out well and is running smoothly in accordance with the activity plan that has been prepared. This activity received a good response from the sub-district head, Keuchik and residents of the village of Sibreh Keumudee Kab. Aceh Besar, as proven by the appreciation and assistance from residents who participated in planting TOGA plants until completion.